Study of Panchayats 1958 - Planning Commission (Planning Commission, 1958)
Statutory panchayats have existed in some States of the country for a fairly long period. Thus, Madras, had its first panchayats in. 1920. Some other States, notably Bombay and Mysore, have also had panchayats for nearly three decades. These earlier panchayats, however, covered only a limited number of villages and had generally a limited range of functions. The programme of organising panchayats on a country-wide scale can be said to have started only after Independence. It was motivated by the objectives of decentralising administration and giving the maximum initiative to the village people in the management of their own affairs and development of their own resources. The idea was incorporated in the Constitution of India as a Directive Principle of State policy : — ‘'The State shall take steps to organise village panchayats and endow them with such power and authority as may be necessary to enable them to function as units of self government”—Article 40— Directive Principles. However, a number of States motivated by the fundamental ideas which were later incorporated in the constitution had already taken steps for establishment of panchayats.
Programme Evaluation Organisation, Planning Commission